2020
DOI: 10.2147/copd.s231808
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Prognostic Role of NT-proBNP for in-Hospital and 1-Year Mortality in Patients with Acute Exacerbations of COPD</p>

Abstract: Background and objective: The association between N-terminal pro B-type natriuretic peptide (NT-proBNP) concentrations and in-hospital and 1-year mortality in acute exacerbations of chronic obstructive pulmonary disease (AECOPD) patients is largely unknown. Our objective was to explore the usefulness of NT-proBNP concentrations in AECOPD patients as a prognostic marker for in-hospital and 1-year mortality. Methods: NT-proBNP levels were measured in patients upon admission and laboratory and clinical data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The RW admission diagnostic procedures including cardiac echo revealed the high frequency of cardiac failure as a cause for the acute deterioration of respiratory symptoms in these patients. None of the cardiac complication that have been reported to occur in AECOPD after admission, such as myocardial infarction or arrhythmias [11,24], occurred in our population, which confirms that cardiac failure, when present, was part of the presenting AECOPD. Several mechanisms such as tachycardia, hypoxemia, increased pulmonary artery pressure, infective exacerbations provoking arterial stiffness have been postulated as causing cardiac distress during AECOPD in subjects with associated cardiac disease [25,26].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The RW admission diagnostic procedures including cardiac echo revealed the high frequency of cardiac failure as a cause for the acute deterioration of respiratory symptoms in these patients. None of the cardiac complication that have been reported to occur in AECOPD after admission, such as myocardial infarction or arrhythmias [11,24], occurred in our population, which confirms that cardiac failure, when present, was part of the presenting AECOPD. Several mechanisms such as tachycardia, hypoxemia, increased pulmonary artery pressure, infective exacerbations provoking arterial stiffness have been postulated as causing cardiac distress during AECOPD in subjects with associated cardiac disease [25,26].…”
Section: Discussionsupporting
confidence: 81%
“…The strong association of underlying cardiovascular comorbidities in any degree of COPD severity suggests that ED management should always include a workup for potential associated cardiovascular events. A high degree of suspicion, past history of cardiovascular diseases, ECG and NT-proBNP, a valuable tool in the diagnosis of HF, are recommended steps to reach a diagnosis of HF, yet it will still be difficult in the presence of COPD [13,24]. In our cohort, the results of NT-proBNP and CRP done during the RW admission, where heart failure was confirmed by the echocardiogram, were similar to the ones done in the ED.…”
Section: Discussionsupporting
confidence: 63%
“…[10] Another study by Hai et al found that NT-pro-BNP level (≥551.35 ng/l) was associated with in-hospital mortality and 1-year mortality in patients with exacerbations of COPD, but in their study, about 35.9% of patients had congestive heart failure. [11] A systematic review and meta-analysis also found that elevated NT-pro-BNP values were associated with all-cause in-hospital mortality in patients with and without exacerbation of COPD. [17] Stolz et al found that BNP was not associated with 6-month or 2-year mortality in patients with exacerbations of COPD, but BNP accurately predicted the need for ICU treatment, and the need for mechanical ventilation was the most common reasons for ICU admission.…”
Section: Discussionmentioning
confidence: 98%
“…[10] Another prospective study showed that NT-pro-BNP level was associated with in-hospital mortality and 1-year mortality in patients with exacerbations of COPD; however, in their studies, about 35.9% of patients had congestive heart failure. [11] Stolz et al found that BNP accurately predicted the need for intensive care unit (ICU) treatment, [12] and BNP was an independent predictor of requirement for noninvasive ventilation, mechanical ventilation, and noninvasive ventilation failure in patients with AECOPD along with preserved left ventricular function. [13] However, some studies have found that NT-pro-BNP level was not associated with the requirement for noninvasive positive pressure ventilation, mechanical ventilation, or in-hospital mortality in patients with AECOPD without underlying left ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, a large number of studies have found that EOS also participates in chronic obstructive pulmonary airway inflammation, so eosinophilic AECOPD is of wide concern in the respiratory community. 3,4 IL-13 and ECP are both cytokines related to EOS inflammation. A large number of animal experiments and clinical studies have shown that both IL-13 and ECP are involved in the pathogenesis of COPD.…”
Section: Introductionmentioning
confidence: 99%